Analisis Kesalahan Berbahasa Tataran Sintaksis di Instagram Kementerian Kesehatan Republik Indonesia - Karina, Agidia; Yuli Yanthi, Erlina; Nurmiyanti, Nurmiyanti; Sinaga, Mangatur (UIR PRESS, 2023)
This study aims to analyze language errors at the syntactic level in the Instagram status of the Ministry of Health of the Republic of Indonesia. The data source used is the Instagram status which contains grammatical errors and grammatical errors. The data collection technique used is to see, observe, and record. Data analysis was performed using qualitative description techniques to explain the forms and causes of syntax errors. The research data amounted to 40, consisting of 14 phrase errors and 26 sentence errors. Based on the results of the analysis, phrasal errors are caused by the use of wrong prepositions, inappropriate wording, and excessive use of elements, while sentence errors consist of sentences without subjects, stump sentences, between predicates and inserted objects, omissions of conjunctions, use of conjunctions that are exaggeration, the use of foreign terms, and the use of unnecessary question words.